Pengaruh Kualitas Pelayanan Mobile Banking Kepada Loyalitas Nasabah dengan Kepuasan Selaku Variable Intervening (Studi Kasus Bsi Kacab Binjai) - Lubis, Mutiara Suci Kesuma; Tambunan, Khairina (Regress: Journal of Economics & Management, 2022)
Service1quality is1one of the key1aspects1of a bank's success, for1that a strategy is needed to improve1service1quality1so that customer1satisfaction and loyalty can be realized, because if satisfaction cannot be achieved by a bank, it means1that the low level of service provided does not lead to customer compliance itself. With Customer Happiness as an intermediary or intervening. This study intends to identify and analyze the impact of the quality of mobile banking services at Bank Syariah Indonesia on customer satisfaction and the 1onsequences for customer loyalty at Bank Syariah Indonesia KC Binjai. The method used is descriptive qualitative. The results of the study found that the simultaneous method is known if m-banking services affect customer satisfaction. The company is obliged to improve every service provided so that customers who use m-banking services feel excessive benefits.